PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI, KOMPLEKSITAS TUGAS, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI - Rofano, Erwin Candra; Setyaningsih Sri Utami, Lamidi & (Universitas Slamet Riyadi, 2018)
The purpose of this study was to analyze the significance: 1) effect of the use of information technology on employee performance. 2) influence of task complexity on employee performance and 3) effect of the work environment on employee performance. This research is a survey. The population of the research is the employees of PDAM Tirto Negoro, Sragen Regency. Samples were 58 people with proportional cluster random sampling technique. Data collection techniques used questionnaires. Data analysis uses multiple linear regression. Descriptive analysis results show that the use of information technology, work environment and employee performance is in good condition while the complexity of the task of the employee is moderate. The use of information technology has a significant effect on the performance of the employees of PDAM Tirto Negoro, Sragen Regency. The task complexity has a significant effect on the performance of the employees of PDAM Tirto Negoro, Sragen Regency. The work environment has a significant effect on the performance of the employees of PDAM Tirto Negoro, Sragen Regency.Keywords: the use of information technology, task complexity, work environment, performance